Implementasi LMS Dalam Media Pembelajaran Menggunakan Moodle Pada MK Media Pembelajaran Ilmu Komputer - Raniyah Ayu Lestari; Dina Dalilah; Aras Adegia (PPPM Institut Teknologi Pagar Alam, 2025)
The implementation of the Learning Management System (LMS) using Moodle in the learning media for the Teaching Media course in the Computer Science Study Program aims to enhance the effectiveness and interactivity of the teaching and learning process. This study examines the application of Moodle as a platform for delivering materials, assignments, and evaluations online. Moodle can be accessed easily by all users. External Learning Resources: To enrich the learning content, Moodle can be integrated with external learning resources such as YouTube, Google Drive, or other learning platforms. Features such as discussion forums, quizzes, and material uploads allow students to learn independently and collaboratively. The results of the study show that the use of this LMS facilitates students' access to information and speeds up feedback from lecturers, making them feel more motivated and have greater control over their learning process. In conclusion, the implementation of Moodle as it positively impacts the quality of learning, increases participation, and prepares them to face challenges in the digital era. It is hoped to serve as a model for the development of online learning in the future.